The Effects of Probiotic Supplementation on Anthropometric Growth and Gut Microbiota Composition in Patients With Prader-Willi Syndrome: A Randomized Double-Blinded Placebo-Controlled Trial - Kong, Xue-Jun; Wan, Guobin; Tian, Ruiyi; Liu, Siyu; Liu, Kevin; Clairmont, Cullen; Lin, Xiaojing; Zhang, Xiaoying; Sherman, Hannah; Zhu, Junli; Wang, Yelan; Fong, Michelle; et al. (Frontiers in Nutrition, 2021)
Background: Prader-Willi Syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Bifidobacterium animalis subsp. lactis has demonstrated anti-obesity and anti-inflammatory effects in previous studies. Aim: To evaluate the effects of Bifidobacterium animalis subsp. lactis probiotics supplementation on anthropometric growth, behavioral symptoms, and gut microbiome composition in patients with PWS. Methods: Ethical Approval was issued by the Internal Review Board (IRB) of the Second Affiliated Hospital of Kunming Medical University (Review-YJ-2016-06). We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 68 patients with Prader-Willi syndrome aged 11 months to 16 years (mean = 4.2 years old) who were randomly assigned to receive daily B. lactis-11 probiotics (6×1010 CFUs) or a placebo sachet. Weight, height, ASQ-3, ABC, SRS-2, and CGI-I were compared between the two groups at baseline and at 6 and 12 weeks into treatment. Gut microbiome data were analyzed with the QIIME 2 software package, and functional gene analysis was conducted with PICRUSt-2. Results: We found a significant increase in height (mean difference = 2.68cm, P < 0.05) and improvement in CGI-I (P < 0.05) in the probiotics group compared to the placebo group. No significant change in weight or psychological measures were observed. Probiotic treatment altered the microbiome composition to favor weight loss and gut health and increased the abundance of antioxidant production-related genes. Conclusions: The findings suggest a novel therapeutic potential for Bifidobacterium animalis subsp. lactis probiotics in Prader-Willi syndrome patients, although further investigation is warranted.